SOSIALISASI KEBIJAKAN KPPU TERKAIT SINERGI BUMN: MEMASTIKAN PERSAINGAN USAHA YANG SEHAT DAN BERKEADILAN - Rafie, Patih Ahmad; Junaidi, Junaidi; Merta, M. Martindo (Transpublika Publisher, 2023)
The primary objective of this community service initiative is to augment public comprehension and awareness, particularly among business entities and stakeholders associated with State-Owned Enterprises (BUMN), regarding the regulations governing fair and robust business competition. The overarching goal is to stimulate greater adherence to these regulations and foster transparency in the operational practices of BUMNs. Through these endeavors, we aim to pinpoint and address challenges inherent in business competition practices, ultimately fostering an environment conducive to innovation and sustainable economic development. The methodology employed in this community service involves the orchestration of a comprehensive series of workshops. These workshops serve as a platform for disseminating knowledge on fair and healthy business competition regulations, elucidating best practices in the synergies of State-Owned Enterprises, and facilitating discussions on compliance and transparency. By creating an open forum for dialogue and learning, participants are equipped with the tools and insights needed to navigate the intricacies of business competition regulations effectively. The tangible outcomes of this community service initiative are multifaceted. Firstly, there is a discernible enhancement in public understanding and awareness of the regulatory framework governing fair and healthy business competition.